Effect of a single application of coumestrol and/or dimethyl sulfoxide, on sex hormone levels and vaginal cytology of anestrus bitches - Sheila Peña-Corona (Veterinaria México, 2019)
Canine overpopulation continues to be a problem with serious public health implications, despite a diversity of programs and strategies that have been implemented for its control. Coumestrol (COU) is an organic compound with estrogenic activity, thus having the potential to alter reproduction in mammals. COU is commonly dissolved in dimethyl sulfoxide (DMSO) before administration; however, evidence indicates that DMSO is not inert. The aim of this study was to assess the effects of either a single oral administration of COU diluted in DMSO or of DMSO-alone, on serum progesterone (P4) and estradiol (E2), on vaginal cell pattern, and on anestrus and diestrus lengths in bitches. Fifteen anestrus female dogs received either a single commercial dog food biscuit (Control, n=5), a biscuit with 600 µg of COU/kg diluted in 20 µL of DMSO (COU, n=5), or a biscuit with 20 µL of DMSO (DMSO, n=5). Circulating P4, E2, and changes in vaginal cytology, were assessed within the first month after treatment administration. Hormone levels were also measured from months 2-6 post-treatment. Mean differences were analyzed by the GLM procedure for repeated measures. COU enhanced serum E2 levels, and DMSO increased serum P4, number of vaginal anucleated superficial cells, and diestrus length. All dogs were deemed healthy based on all periodical clinical exams, but abnormal mammary gland growth and/or galactorrhea were observed in two COU and one DMSO-treated bitches. The findings of the present study expose the need to reevaluate previous reports of use of COU in bitches, and perhaps in other mammals.